Performance analysis of cognitive radio spectrum access with prioritized traffic - Tumuluru, Vamsi Krishna (2013)
Dynamic spectrum access (DSA) is an important design aspect for cognitive radio networks. Most of existing DSA schemes are to govern unlicensed user (i.e., secondary user, SU) traffic in a licensed spectrum without compromising the transmissions of the licensed users, in which all the unlicensed users are typically treated equally. In this paper, prioritized unlicensed user traffic is considered. Specifically, the unlicensed user traffic is divided into two priority classes (i.e., high and low priority). We consider a general setting in which the licensed users' transmissions can happen at any time instant. Therefore, the DSA scheme should perform spectrum handoff to protect the licensed user's transmission. Different DSA schemes (i.e., centralized and distributed) are considered to manage the prioritized unlicensed user traffic. These DSA schemes use different handoff mechanisms for the two classes of unlicensed users. We also study the impact of subchannel reservation for high-priority SUs in both DSA schemes. Each of the proposed DSA schemes is analyzed using a continuous-time Markov chain. For performance measures, we derive blocking probability, the probability of forced termination, call completion rate, and mean handoff delay for both high- and low-priority unlicensed users. The numerical results are verified using simulations.